Communication—Controlling Highly Dominated N Configuration in N-Doped Graphene as Oxygen Reduction Catalyst. Issue 4 (31st January 2017) - Hu, Baoshan; He, Xiaoying; Wu, Rui; Jin, Yan; Bian, Yawei; Chen, Siguo; Wei, Zidong
Abstract : Pyridinic-, pyrrolic-, and nitrile- N doped graphene films with each dominance of more than 80 at% are successfully synthesized with a simple flash heating-assisted CVD process. Moreover, the three N configurations can be facilely tuned by the variation of reaction time and the participation of methane. Deep investigation elucidate that pyridinic-N is responsible for the ORR activity in good agreement with other investigations.